2017
DOI: 10.1080/03630242.2017.1372843
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with residential mobility during pregnancy

Abstract: Our objective was to determine the factors associated with residential moving during pregnancy, as it may increase stress during pregnancy and affect birth outcomes. Data were obtained from the Conditions Affecting Neurocognitive Development and Learning in Early Childhood (CANDLE) study. Participants were recruited from December 2006 to June 2011 and included 1,448 pregnant women. The average gestational age at enrollment was 23 weeks. The primary outcome of residential mobility was defined as any change in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The primary limitation of this study was our inability to control for the duration women resided in their respective neighborhoods. Previous research supports 12 to 41% of women moved during pregnancy [60][61][62][63][64][65][66]; however, Black families, particularly those of low income, are more likely to move to similar neighborhoods compared to White families [66][67][68]. Additionally, the differing gradient of risk associated with ICE measures can be due to the modifiable areal unit problem (MAUP) [69][70][71].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The primary limitation of this study was our inability to control for the duration women resided in their respective neighborhoods. Previous research supports 12 to 41% of women moved during pregnancy [60][61][62][63][64][65][66]; however, Black families, particularly those of low income, are more likely to move to similar neighborhoods compared to White families [66][67][68]. Additionally, the differing gradient of risk associated with ICE measures can be due to the modifiable areal unit problem (MAUP) [69][70][71].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, our study did not address the issue of mobility during pregnancy. Several studies on this topic found that between 5 and 25% of women moved at least once during pregnancy (Tang et al 2018;Lara et al 2016;Amoah et al 2018;Pereira et al 2016;Bell and Belanger 2012). This means that some of the locations in some space-time bins may not be representative of the entire duration of a pregnancy and may cause misleading trends in either direction.…”
Section: Discussionmentioning
confidence: 99%